Manajemen Anestesi pada Percutaneus Endoscopic Lumbar Discectomy (PELD) dengan Dexmedetomidine - Sari, Djayanti; Wisudarti, Calcarina Fitriani Retno; Ferdiansyah, David (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
The patient is 49 years old with a diagnosis of Hernia Nucleosus Pulposus (HNP) 4-5 lumbar vertebrae. The patient was scheduled to undergo the PELD procedure. The anesthetic technique used is total intravenous anesthesia (TIVA) with dexmedetomidine. The dose used is loading 1 mcg per kg body weight in 10 minutes followed by titration of 0.2-0.7 mcg/kg body weight/hour. During the procedure the operator requires confirmation from the patient to prevent complications of nerve injury. The action lasts about 2 hours in the prone position. The level of sedation was assessed by the Ramsay scale score. Hemodynamics during the procedure is stable and the patient is quite comfortable.